Shifting Feeding Habits During Settlement Among Small Yellow Croakers (Larimichthys polyactis) - Yuange Chen; Weilong Wang; Wei Zhou; Fen Hu; Meiqin Wu (Frontiers in Marine Science, 2022)
The small yellow croaker, Larimichthys polyactis, is a keystone species in the Yellow Sea and the East China Sea, with significant impacts on the regional ecosystem, but has experienced decades of population decline as a result of environmental changes and overfishing. The settlement of post-larval L. polyactis is a period of high mortality, with impacts on population recruitment and survival. This study examines the feeding habits of 49 post-larval and early juvenile L. polyactis in the Yangtze River estuary, in order to reveal diet composition before and after the settlement period. DNA barcoding methods (MiSeq and TA cloning) were used to examine gastrointestinal contents in detail. Both methods revealed that dietary breadth increased with increasing body length, while the dominance of copepods in the diet decreased as the body length increased. Post-larva (body length < 17 mm in this study) primarily fed on copepods. At the beginning of settlement (body length between 17 and 19 mm), L. polyactis began to ingest larger organisms, such as fishes and mysids, along with copepods. Larger early juveniles (body length > 20 mm) demonstrated a much wider dietary breadth, implying that successful settlement had occurred. Diet species richness in the MiSeq group was significantly greater than species richness in the TA cloning group, making the trend more pronounced within the MiSeq group. This indicates that the MiSeq method was more efficient than TA cloning in this study. We recommend that future research to investigate the feeding habits of fish larvae should combine MiSeq and visual examination methods.